Pregnancy Pharmacovigilance: Safety Monitoring of Drugs and Vaccines in Maternal Health - Dhobale, Anchal S.; Shelake, Akash Kailas (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
Pharmacovigilance in maternal health is essential for evaluating the safety of medications and vaccines used during pregnancy. Since pregnant individuals are typically excluded from clinical trials for ethical and safety reasons, there is very limited pre-marketing safety information available. This gap in evidence makes it difficult to fully understand the potential effects of drugs and vaccines on both mothers and their babies, highlighting the importance of post-marketing surveillance. To gather safety data, maternal pharmacovigilance uses both passive and active monitoring methods, including spontaneous reporting systems, pregnancy exposure registries, and observational cohort studies. Record-linkage studies and surveillance systems help compare outcomes between exposed and unexposed groups, enabling the identification of possible risks or adverse events. However, low- and middle-income countries face additional barriers such as limited infrastructure, inadequate resources, dependence on passive reporting, and the absence of standardized protocols. Strengthening these systems through better policies, workforce training, improved data integration, and collaboration among stakeholders is crucial for generating robust real-world evidence. Such improvements support informed clinical decision-making and ensure safer use of medicines and vaccines during pregnancy.